Understanding Family Business Dynamics: The Role of Family Business Embeddedness and Organizational Justice in Reducing Turnover Intention through Job Satisfaction - Tata Kartikasuri, Dyan; Suryanto , Suryanto (Ekonomi dan Bisnis, 2024)
Family businesses are unique business entities due to the complex interplay between family and business factors. In family businesses, companies are owned, operated, and controlled by family members, often creating interpersonal dynamics not found in non-family businesses. This study aims to explore the impact of family business embeddedness and organizational justice on turnover intention, both directly and indirectly, through job satisfaction as a mediator. The method used in this research is quantitative, with a sample size of 68 respondents. The results of this study reveal that family business embeddedness has a positive and significant effect on job satisfaction and a negative and significant effect on turnover intention. Organizational justice has a positive and significant effect on job satisfaction and a negative and significant effect on turnover intention. Job satisfaction negatively and significantly affects turnover intention. Furthermore, there is a significant impact of family business embeddedness and organizational justice on turnover intention through job satisfaction. Practical and theoretical implications, as well as the limitations of the study, are discussed in this research.